PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI PADA SUKU DINAS PENDIDIKAN WILAYAH I KOTA ADMINISTRASI JAKARTA SELATAN - Kusnendar, Dede; Nofiar (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of motivation and discipline on employee performance at the South Jakarta Administrative City Region I Education Sub-Department, either partially or simultaneously. The method used is quantitative. The sampling technique used saturated sampling, namely as many as 65 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are motivation has a significant positive effect on employee performance with the regression equation Y = 16.352 + 0.588X with a correlation coefficient value of 0.676 meaning that it has a strong relationship with an influence contribution of 45.7% and the hypothesis test obtained is t count > t table or ( 7.280 > 1.998). Discipline has a significant positive effect on employee performance with the regression equation Y = 13.120 + 0.677X with a correlation coefficient value of 0.705 meaning that it has a strong relationship with an influence contribution of 49.7% and the hypothesis test obtained is t count > t table or (7.887 > 1.998) . Motivation and discipline simultaneously have a significant positive effect on employee performance with the regression equation Y = 7.673 + 0.363X1 + 0.461X2 with a correlation coefficient value of 0.788 meaning that it has a strong relationship with an influence contribution of 62.0% while the remaining 38.0% is influenced another factor. Hypothesis testing obtained F count > F table or (50.667 > 2.750).